Analysis Of Factors That Influence Online Purchasing Decisions In The Millennium - Rini Astuti; Linzzy Pratami Putri (Journal of International Conference Proceedings (JICP), 2019)
This study aims to determine what factors influence the decision of consumers (millennial generation) to make online purchases. The population in this study is the millennial generation born in the 2000s. The research method used is quantitative descriptive using factor analysis techniques. Where the results of the study stated that there are three dominant factors that influence online purchasing decisions, namely lifestyle,easiness, and quality of information.